Melancholia : the diagnosis, pathophysiology, and treatment of depressive illness - Taylor, Michael Alan, 1940- (Cambridge University Press, 2006)
This book provides a comprehensive review of melancholia as a severe disorder of mood, associated with suicide, psychosis and catatonia. The syndrome is defined with a clear diagnosis, prognosis and range of management strategies. It challenges accepted doctrines and describes melancholia as a treatable and preventable mental illness.